Personalization at scale : challenges and practical techniques (O'Reilly Media, 2019)
"Hagay Lupesko explores AI-powered personalization at Facebook and the challenges and practical techniques it applied to overcome these challenges. You'll learn about deep learning-based personalization modeling, scalable training, and the accompanying system design approaches that are applied in practice. This session is from the 2019 O'Reilly Artificial Intelligence Conference in San Jose, CA."--Resource description page